Low-density lipoproteins supply phospholipid-bound arachidonic acid for platelet eicosanoid production - Dobner, P. (Universitat Munchen, Munich, Germany.); Engelmann, B (American journal of physiology: endocrinology and metabolism, 1998)
Physiologisches Institut der Universität München, D-80336 Munich, Germany After the rapid extracorporal reduction of plasma low-density lipoprotein (LDL) by LDL apheresis, the percentages of arachidonic acid (AA)-containing species of phosphatidylcholine (PC) were lowered in the plasma of patients with hypercholesterolemia. The same PC species with AA were also decreased in the patient's platelets. Thus the supply of phospholipid-bound AA from LDL to the platelets was probably diminished after the apheresis. We therefore analyzed the concentration dependence of the transfer of phospholipid-bound AA from LDL to the platelets under in vitro conditions. The amount of [ 14 C]AA-PC transferred to platelets strongly increased upon elevation of LDL from 0.1 to 1 mg protein/ml, with a less marked elevation being noted at higher LDL concentrations. After stimulation with thrombin (0.5 U/ml), 7.1% ([ 14 C]AA-PC) and 10.6% ([ 14 C]AA-phosphatidylethanolamine) of the 14 C transferred from LDL to the platelets were recovered in the eicosanoids [ 14 C]thromboxane B 2 (TxB 2 ) plus 12-[ 14 C]hydroxyeicosatetraenoic acid. Experimental increases and reductions of the [ 14 C]AA-PC import were associated with comparable modifications in the [ 14 C]TxB 2 production of the platelets. Accordingly, the import of phospholipid-bound [ 14 C]AA is a necessary prerequisite for the formation of 14 C-labeled eicosanoids. In summary, the transfer of phospholipids from LDL to the platelets markedly varies within the physiological range of lipoprotein concentrations. LDL contributes to platelet eicosanoid formation by supplying platelets with phospholipid-bound AA. [ 3 H]arachidonic acid; 125 I-labeled apoprotein B; phosphatidylinositol; sphingomyelin; phospholipase A 2